2016
DOI: 10.20546/ijcrbp.2016.311.005
|View full text |Cite
|
Sign up to set email alerts
|

Study of Synergy between Mentha pulegium Essential Oil, Honey and Bacteriocin-like Inhibitory Substance E204 against Listeria monocytogenes CECT 4032 and Escherichia coli K12

Abstract: A b s t r a c t A r t i c l e I n f oThe research was undertaken to determine the possible synergistic interactions between any two antibacterial agents; Mentha pulegium essential oil (MPEO), honey and bacteriocin-like inhibitory substance (BLIS) E204 against Escherichia coli K12 and Listeria monocytogenes CECT 4032. The antibacterial activity was evaluated using the broth micro-dilution method, and the interaction was determined by the fractional inhibitory concentration (FIC) indexes. The results obtained sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Then, honeys concentrations are introduced vertically into eight wells in a decreasing manner going from MIC × 2 to MIC/64, while the essential oil concentrations are introduced horizontally into seven wells in a decreasing fashion from CMI × 2 to CMI/16. The analysis of the combination was obtained by calculating the fraction inhibitory concentration index (FIC) using the following formula [ 26 ]: FIC ( A ) = (MIC ( A ) in combination/MIC ( A ) alone); FIC ( B ) = (MIC ( B ) in combination/MIC ( B ) alone). The index values of the fractional inhibitory concentrations are interpreted as follows: FIC ≤ 0.5 = Synergy; FIC < 0.5–0.75 ≥= partial Synergy; FIC ≤ 0.76–1.0 >= Additive; FIC > 1–4 ≤= No interaction (not differential) and FIC > 4 = Antagonism.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, honeys concentrations are introduced vertically into eight wells in a decreasing manner going from MIC × 2 to MIC/64, while the essential oil concentrations are introduced horizontally into seven wells in a decreasing fashion from CMI × 2 to CMI/16. The analysis of the combination was obtained by calculating the fraction inhibitory concentration index (FIC) using the following formula [ 26 ]: FIC ( A ) = (MIC ( A ) in combination/MIC ( A ) alone); FIC ( B ) = (MIC ( B ) in combination/MIC ( B ) alone). The index values of the fractional inhibitory concentrations are interpreted as follows: FIC ≤ 0.5 = Synergy; FIC < 0.5–0.75 ≥= partial Synergy; FIC ≤ 0.76–1.0 >= Additive; FIC > 1–4 ≤= No interaction (not differential) and FIC > 4 = Antagonism.…”
Section: Methodsmentioning
confidence: 99%
“…The extensive investigation of the antimicrobial activities of honey and essential oils against a large category of bacterial and fungal pathogenesis is extended to test the combinations of both natural products [ 25 , 26 ]. In all those studies it is found that there are positive interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Each association was performed in duplicate. e analysis of the combination was obtained by calculating the fractional inhibitory concentration (FIC) index (FICI) using the following formula [27] e index values of the fractional inhibitory concentrations were interpreted as follows: FICI ≤ 0.5 means synergy; 0.5 < FICI ≤ 0.75 means partial synergy; 0.76 ≤ FICI ≤ 1 means additive effect; 1 < FICI ≤ 4 means no interaction (not differential); FICI > 4 means antagonism.…”
Section: Checkerboard Assaymentioning
confidence: 99%
“…Thus, many recent studies have investigated the pharmacological properties, such as antimicrobial [24][25][26], anticancer [27,28], antidiabetic [29][30][31], and analgesic [32,33] effects of various Moroccan plants, and several studied their anti-inflammatory potential [34][35][36]. Rare are the studies carried out on the association between honey and essential oils (EOs) or plant extracts [18,[37][38][39][40][41]. None of them investigated the synergistic effect between honey and EOs for the treatment of inflammation.…”
Section: Introductionmentioning
confidence: 99%